THE HUSBAND POSITION IN BAJAPUIK MARRIAGE DYNAMICS IN PARIAMAN - Restia Gustiana (Jurnal Ilmiah Al-Syir'ah, 2020)
This research conducted to see the position of the husband in a traditional Pariaman marriage known as a Bajapuik marriage. Pariaman is a part of the Minangkabau region, which had opted for the matrilineal system, which affects customary marriages, namely, after marriage, some rights and obligations of the husband are more controlled by the mamak (chiefs who come from the wife's family). This study uses qualitative research in a field research system (Field Research) with an anthropological (ethnographic) approach. The subject of this study leads to key informants that researcher chooser and only (random) based on specific criteria and categories that can describe condition subjectively in the field. The findings of this study indicate that Bajapuik marriage affects the position of the husband in the family. The husband's position in family decisions only an input because the husband is considered a newcomer. The findings of this study reinforce the opinion of Poloma, an action someone will get social sanctions that is along with the times the husband's position began to shift as well as mamak. Mamak is no longer able to carry out her role all rights and obligations are handed over to her husband as well as her husband, who had previously had no burden in providing for his wife and children, bécame an obligation.